Public food procurement as a tool of sustainable food and nutrition policy—fat products - Brukało, Katarzyna Magdalena; Nowak, Justyna; Pietrzykowska, Aleksandra; Fras, Neza; Ožbolt, Petra; Kowalski, Oskar; Blenkuš, Mojca Gabrijelčič (Frontiers in Sustainable Food Systems, 2024)
Introduction Ensuring a sustainable and responsible diet, particularly in the procurement of fatty products, holds paramount importance for early childhood development. Dietary fats significantly influence children’s growth and well-being, both in the short and long term. Schools and kindergartens play a pivotal role in shaping children’s dietary habits. This study aims to quantitatively and qualitatively analyze public procurement orders conducted by educational institutions. Materials and methods Out of 1,126 public procurement orders, 197 met inclusion criteria, leading to the identification of 1,248 products categorized as sources of fats in children’s diets. The study conducted both quantitative and qualitative analyses on the identified products. Results Criteria commonly employed by purchasers were derived from product descriptions. While product composition, especially fat content and the absence of certain additives, received due attention, organoleptic characteristics criteria were frequently overlooked. Sustainable procurement criteria were given the least consideration. The study highlights a notable reliance on vegetable oils, predominantly rapeseed oil. However, it reveals a worrisome prevalence of animal-derived fats, including butter, mayonnaise, pork belly, and lard. Although plant-based fats constitute around 52.77% of total orders, the substantial presence of animal fats poses challenges to maintaining a balanced and healthy diet for children. Conclusion The study underscores the necessity of establishing specific criteria for evaluating the quality of delivered products, especially fatty items, in educational settings. Standardized guidelines are crucial to promote healthier food choices, encourage sustainable diets, and ultimately enhance the overall health and well-being of children.